The Relationship Between Duration of Type 2 Diabetes and HbA1C with the Incidence of Diabetic Ulcers in Diabetes Patients at Roemani Hospital - Ali Ridwan Rohmatullah; Alif Adlan Zulizar; Rifka Widianingrum (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Background: Type 2 diabetes mellitus (DM) is a chronic disease that can cause various complications, one of which is diabetic ulcers. Long-term DM and poor glycemic control, as indicated by high HbA1C levels, are thought to contribute to the development of diabetic ulcers. Methods: This study employed an observational analysis approach with a cross-sectional design. The data collection method used total sampling, with 86 samples drawn from the total population. Analysis used the Spearman Rank test with a 95% confidence level and a margin of error of 0.05. Results: The majority of respondents were aged 40–60 years, with a duration of DM ≥5 years (73.3%), HbA1C >6.4% (75.6%), and grade 1 diabetic ulcers (26.7%). Spearman rank analysis results showed a significant relationship between the duration of type 2 DM and the incidence of diabetic ulcers (r = 0.267; p = 0.01) and a significant relationship between HbA1C and the incidence of diabetic ulcers (r = 0.482; p = 0.01). Conclusion: There is a relationship between the duration of type 2 DM and HbA1C with the incidence of diabetic ulcers in type 2 DM patients at Roemani Hospital